THE PRACTICAL APPLICATION OF INTERACTIVE METHODS IN THE STUDY OF PROFESSIONAL SUBJECT AT FLIGHT HIGHER SCHOOL - Смирнова, І. Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted to the analysis of the benefits of interactive methods in learning professional subjects at flight higher school. The author of the article gives a brief review of the complex of interactive methods, which can be considered as one of the efficient ways of increasing of level of professional knowledge preparation at flight higher school. Interactive learning methods contribute to stimulate cognitive interest of students, encouraging expression, finding arguments to defend their position, taking into account the opposite view in the interactive group activities